Ophiacantha aristata Koehler 1895 - Madeira, Patrícia; Kroh, Andreas; Cordeiro, Ricardo; De, António M.; Martins, Frias; Ávila, Sérgio P. (Zenodo, 2019)
Ophiacantha aristata Koehler, 1895c Reports for the Azores: Ophiacantha aristata Koehler, 1895 c— $ Koehler 1896a: 212, 1898: 55, 1906b: 288–289, 1909: 183, pl. 26, figs. 5–6, 1921a: 2; Mortensen 1927a: 191, 193–194, fig. 107; Grieg 1932: 38; Nobre 1938: 76–77; García-Diez et al . 2005: 49. Type locality: Bay of Biscay. See: Koehler (1896c: 81–86, figs. 43, 44); Rodrigues et al . (2011: 7, fig. 2). Occurrence: Northeast Atlantic, from the Reykjanes Ridge (S of Iceland; Copley et al . 1996) and British Isles to NW Africa (Paterson 1985), including the Azores and Canaries (Koehler 1909). Depth: 658– 1,805 m (Copley et al . 1996); AZO: 1,095 –1,740 m (Koehler 1909, 1921a). Habitat: soft bottoms, mud to sand (Koehler 1909) and on corals (Rodrigues et al . 2011). Remarks: Koehler (1896a, 1898, 1906b, 1909, 1921a) recorded Ophiacantha aristata among the material collected by the main oceanographic cruises crossing the Azorean archipelago waters at the time ( Hirondelle , Talisman , Princesse Alice ). This species is only known in the archipelago from Koehler’s historical reports. Published as part of Madeira, Patrícia, Kroh, Andreas, Cordeiro, Ricardo, De, António M., Martins, Frias & Ávila, Sérgio P., 2019, The Echinoderm Fauna of the Azores (NE Atlantic Ocean), pp. 1-231 in Zootaxa 4639 (1) on page 33, DOI:10.11646/zootaxa.4639.1, http://zenodo.org/record/3342161